Separation between Ownership and Control and its relation to Value and Performance of Brazilian Companies: where do we stand? - Peixoto, Fernanda Maciel; Buccini, Aline Rabelo Assis (Revista de Contabilidade e Organizações, 2013)
Initially this research performs a diagnosis of the current situation of ownership and control structure of Brazilian public companies traded on the São Paulo Stock Exchange in 2004, 2006 and 2008. Then, it seeks to identify a possible relationship between the concentration of voting rights and the concentration of rights over the cash flow with performance and value of the companies. For that purpose, it uses panel data analysis aiming to relate ownership structure variables and performance/value variables (Tobin's Q, Return on Assets and Price to Book Ratio). As a result, it was noticed that in Brazil there is still high concentration of control in the hands of a few shareholders. However, the percentage of companies with this profile has been decreasing in the studied period. The available capital over total capital ratio has also been decreasing, which is positive for corporate governance. Shareholders of family, private and state-owned companies have been losing ground in the ownership structure of organizations, giving rise to institutional, foreign and spread-out investors. With regard to the relationship between ownership structure and value/performance, it was found that firms with more concentrated structure have lower value and lower performance.